Embodying sensemaking: Learning from the extreme case of Vann Nath, Prisoner at S-21 - Cunha, Miguel Pina e (2022)
The sensemaking literature offered important critical insights to the understanding of organizing. These have been underpinned by two foundational assumptions. First, sensemaking is predominantly a higher order cognitive process. Second, it is a process desired and desirable. Considering the account of Vann Nath as prisoner of the S-21 extermination center during the Khmer Rouge regime, we challenge these assumptions and argue that, in some cases, sensemaking is fundamentally a bodily and emotional process, one that is undesired and blocked by theorganization in which it takes place. The shift in perspective triggered by an extreme context has pertinent implications for the understanding of sensemaking in other, non-extreme organizational circumstances.